Graceful Exits: Spirit Possession as Personal Performance in Mayotte - Lambek, Michael (Culture, 1988)
In what ways can spirit possession among the Malagasy speakers of Mayotte (Comoro Islands, East Africa) be said to be a creative performance? Situating trance episodes in the broader life context of the performer enables us to see that style is in large part a product of frame management. A good performer provides a clear and resonant articulation of her identities as character, medium, and person. Such an articulation is examined at two problematic moments—the closing of a possession ceremony and the closing of a career in old age. The focus on exits marks a departure from the epidemiological slant characteristic of much of the literature and provides a novel way of dealing with trance practice in a non-deterministic framework.